2002
DOI: 10.17660/actahortic.2002.586.180
|View full text |Cite
|
Sign up to set email alerts
|

Detection by Elisa of Predators of Prays Oleae (Lepidoptera: Plutellidae) in a Portuguese Olive Orchard

Abstract: Over 900 predators were collected during two years from a Portuguese organic olive orchard, and tested in a serological bioassay for Prays oleae predation.The highest number of predators tested positive during the phyllophagous and antophagous generations of P. oleae. Ants were the most commonly found predators, followed by Coleoptera, Hemiptera and spiders. INTRODUCTIONOlive is an important crop in Portugal, grown over a surface of 360 000 ha. Among its pests, Prays oleae (Lepidoptera: Plutellidae), is the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
0
2
0
1
Order By: Relevance
“…Some authors have suggested that natural or semi-natural habitats at the landscape scale are important elements that favor the prospection of natural enemies of olive pests by providing undisturbed areas that offer shelter from crop disturbances as well as overwintering refuges, alternative hosts, and prey, and additional food resources [7,19,54]. The assemblage of natural enemies of P. oleae not only includes C. carnea, but also other common predators of the olive moth such as ants, Coleoptera, Hemiptera, and spiders [55]. As described by Paredes et al (2015) [56], effective assemblages of natural enemies are better suppressing a Lepidopteran pest, such as P. oleae than a species of natural enemies acting alone.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have suggested that natural or semi-natural habitats at the landscape scale are important elements that favor the prospection of natural enemies of olive pests by providing undisturbed areas that offer shelter from crop disturbances as well as overwintering refuges, alternative hosts, and prey, and additional food resources [7,19,54]. The assemblage of natural enemies of P. oleae not only includes C. carnea, but also other common predators of the olive moth such as ants, Coleoptera, Hemiptera, and spiders [55]. As described by Paredes et al (2015) [56], effective assemblages of natural enemies are better suppressing a Lepidopteran pest, such as P. oleae than a species of natural enemies acting alone.…”
Section: Discussionmentioning
confidence: 99%
“…türlerinin zeytin bahçelerinin önemli bir zararlısı olan zeytin güvesi Prays oleae (Praydidae)'nın yumurta ve larvaları ile beslendikleri de ifade edilmiştir. Lozano et al (2000), İtalya'daki zeytin bahçelerinde çukur tuzaklarla yapılan bir çalışmada 18 familyaya ait 70 örümcek türü tespit etmişlerdir. Bunlardan Linyphiidae, Lycosidae, Dysderidae, Gnaphosidae ve Theridiidae familyalarının en baskın familyalar olduğunu ifade etmişlerdir.…”
Section: Introductionunclassified
“…Serological arthropod gut analyses, such as the enzyme-linked immunosorbent assay (ELISA), have been widely used to investigate predation on invertebrates offering a rapid identification of the remains of specific prey in the guts of predators (Fichter and Stephen 1981;Sunderland et al 1987;Sopp et al 1992;McIver and Tempelis 1993;Symondson and Liddell 1993;Symondson et al 1996;Morris et al 1999). Serological tests were successfully used in olive groves to study the natural enemies of the olive moth, Prays oleae (Bernard), whose main predators were found to be Formicidae, Heteroptera and Coleoptera (Morris et al 1999;Lozano et al 2002).…”
Section: Introductionmentioning
confidence: 99%